Managing external contributors in workforce ecosystems - Altman, Elizabeth J.; Kiron, David; Jones, Robin; Cantrell, Sue; Hatfield, Steve (MIT Sloan Management Review, 2023)
Many executives are struggling to determine the extent to which they should integrate the management of employees and external contributors. The MIT SMR-Deloitte Future of the Workforce team looks at Cisco as a case example of one organization focused on a more strategic integration of its contingent workforce.
"Reprint 64403.". - Includes bibliographical references
Keywords: Independent contractors; Personnel management; Temporary employees; Entrepreneurs indépendants; Personnel; Direction; Travailleurs temporaires